Simulation of automatic fan with LM35 temperature sensor using ATMEGA8535 microcontroller in Proteus application - Aljo Leo Nardo; Weri Sugianto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
The human body actually has a temperature and always releases energy at any time, especially body heat. Humans always react when heat occurs either due to temperature or other things. When heat is generated from the temperature of the air, then humans usually prefer a solution to use a fan as a cooler and conditioner to eliminate the feeling of heat that is felt. But the fan that is often used sometimes makes us bother to turn it on or off. So that an automatic fan is made by utilizing a microcontroller-based temperature sensor equipped with a temperature sensor LM35, ATmega8535 and other circuits that are put together then run. The fan can work automatically with the aim that humans are made easier in the process of activating the fan without having to bother and more efficient in energy use because the fan is only needed if the temperature sensor detects the temperature that has been set. From the results of tests conducted on the simulation the system can work very well according to what has been made. The role of sensors, series, is very important in the success of this project.